PENERAPAN MODEL PJBL BERBANTUAN MEDIA YOUTUBE UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SENI RUPA SISWA KELAS II SD INPRES PALUPI - Siti Soleha; Arif Firmansyah; Renawati (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to improve student learning outcomes through the application of the Project-Based Learning (PJBL) model assisted by YouTube media in fine arts learning in class II of SD Inpres Palupi. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, where each cycle consists of the planning, implementation, observation, and reflection stages. The subjects of the study were 30 class II students. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively to assess the improvement in student learning outcomes. The indicator of the success of this study is the achievement of at least 80% of students with learning outcomes that meet good criteria. The results of the study showed that the application of the PJBL model with YouTube media significantly improved student learning outcomes, as seen from the increase in the percentage of achievement from 40% or 12 students completing the pre-cycle, 66% or 20 students in Cycle I, and 97% or 29 students in Cycle II. These findings indicate that the use of interactive and interesting video-based learning media can improve student understanding and involvement in the learning process. Therefore, it is suggested that the YouTube-assisted PJBL model be used more widely in learning to support improving student learning outcomes.